The effect of the global financial crisis on preventable hospitalizations among the homeless in New York State. Issue 2 (April 2018) - White, Brandi; Ellis, Charles; Jones, Walter; Moran, William; Simpson, Kit
Objective: Periods of economic instability may increase preventable hospitalizations because of increased barriers to accessing primary care. For underserved populations such as the homeless, these barriers may be more pronounced due to limited resources in the health care safety net. This study examined the impact of the global financial crisis of 2007–2008 on access to care for the homeless in New York State. Methods: Hospitalizations for ambulatory care sensitive conditions (ACSCs) were used as a proxy measure for primary care access. Admissions for ACSCs were identified in the New York State Inpatient Database from 2006 to 2012. Hospitalization rates for ACSCs were calculated for the homeless and nonhomeless. Multivariable linear regression was used to investigate the impact of the financial crisis on hospitalization rates for ACSCs. Results: The findings indicate that during the financial crisis, homeless adults had significantly higher preventable hospitalizations than nonhomeless adults, and the uninsured homeless had significantly higher preventable hospitalizations when compared to other homeless subgroups. After the financial crisis, preventable hospitalizations for the homeless stabilized but remained at higher rates than those for the nonhomeless. Conclusions: These findings are important to developing health policies designed to provide effective care for underserved population such as the homeless.